Welfare characteristics of laying hens in aviary and cage systems - Hyelim Jeon; Hyeonwook Shin; Juho Lee; Junsik Kim; Sarbani Biswas; Jungwon Lee; Jinhyeon Yun (Poultry Science)
Concerns regarding the welfare of laying hens in cage systems (CS) have prompted the development of alternative housing systems, such as aviary systems (AS). However, debate remains about welfare and productivity under both systems. This study compares the welfare and egg quality of laying hens in CS and AS. Hy-Line Brown hens housed in CS (n = 79,500; cage space = 0.075 m2/hen; 6.14 hens/cage) and AS (n = 42,079; floor space = 9 hens/m2) on a single farm were evaluated at 28, 38, and 48 weeks of age. Five evaluators from the Welfare Quality® protocol were used to assess physical conditions (n = 600), and behaviors were assessed through qualitative behavior assessment (n = 15 flocks), avoidance distance test (ADT; n = 315), and novel object test (NOT; n = 15 flocks). Additionally, blood parameters (n = 50), egg quality (n = 50), and serum (n = 50) and egg yolk (n = 90) corticosterone levels were measured. Feather condition in CS hens deteriorated with age, showing higher plumage damage scores than AS hens, though both systems showed increases in comb pecking wounds and feather damage over time. The AS hens showed more positive behaviors, e.g., being active and energetic, while CS hens exhibited more negative behaviors, e.g., fearfulness and depression. In the AS, hens responded more quickly to the observer in the ADT (P < 0.01 for all periods), and more approached the object in the NOT (P < 0.01 at 38 and 48 weeks). The CS hens had higher yolk corticosterone levels (P < 0.05) at 48 weeks but produced heavier eggs consistently across all periods (P < 0.01 for all). In conclusion, this study highlights the importance of evaluating laying hen welfare through a combination of behavioral, physical, and physiological measures. Our findings suggest that the AS provides better welfare outcomes for hens than the CS, offering critical insights for improving both animal welfare and productivity in future housing systems.